2021
DOI: 10.1088/1742-6596/1816/1/012116
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the radiation parameters of pumice constituent compounds using XCOM

Abstract: In this study, analysis of radiation parameters (linear attenuation coefficient, mean free path and half value layer) of pumice constituent compounds was carried out. Analyzes were done on the compounds of Al2O3, Fe2O3, SiO2, CaO, K2O and Na2O with a theoretical approach using the XCOM program for gamma photon energies 57Co (0.122 MeV; 0.1365 MeV), 133Ba (0.356 MeV), 54Mn (0.835 MeV), 137Cs (0.662 MeV), 60Co (1.173 MeV; 1.333 MeV), 65Zn (1.1155 MeV), 22Na (0.511 MeV; 1.275 MeV) and 40K (1.461 MeV). The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Having said all of the above, the existing researches mainly focus on basalt fiber reinforced composites, although there are some research on basalt fiber itself, there are no in-depth studies. Different oxides possess different mass attenuation coefficients [ 21 ]. Studies have shown that the increased content of oxides, such as TiO 2 , Fe 2 O 3, and K 2 O, can greatly strengthen the gamma ray shielding property of the glass or alloy materials [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Having said all of the above, the existing researches mainly focus on basalt fiber reinforced composites, although there are some research on basalt fiber itself, there are no in-depth studies. Different oxides possess different mass attenuation coefficients [ 21 ]. Studies have shown that the increased content of oxides, such as TiO 2 , Fe 2 O 3, and K 2 O, can greatly strengthen the gamma ray shielding property of the glass or alloy materials [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%